Production of Bioethanol From Kappaphycus alvarezii Algae by Using Pichia kudriavzevii Yeast - Nur Fadillah; WInda Lestari Taufan; Muh Syahdan Aska (International Journal of Applied Biology, 2018)
Kappaphycus alvarezii is a red algae that can be used as alternative raw material for bioethanol production. This is because K. alvarezii contains a high carbohydrate that reaches 60%. This study aims to determine the effect of fermentation nutrition and fermentation duration of hydrolysis results of K. alvarezii algae on pH changes, sugar levels, cell biomass and ethanol content. There are two methods was used in this research, namely hydrolysis method and fermentation method. The hydrolysis method was used α-amylases enzyme which is 150 KNU/L with 0.5%, 1.0%, 1.5% and 2.0% concentrations. The next method, K. alvarezii algae was fermented by Pichia kudriavzevii and used Gandasil-D® as an anorganic suplementation and yeast extract which is 0 g/L, 1 g/L, 2 g/L and 3 g/L. The results showed that         K. alvarezii can be fermented into bioethanol after enzymatic hydrolysis process. The optimal ethanol content was produced at 48 hours of incubation duration.